The Formation of a Body’s Neoliberal Sensibility: Fragments of an Individual Commodification (Andamios, Revista de Investigación Social, 2025)
This text explores the shaping of a neoliberal sensibility in body intervention practices in Uruguay. It analyzes how state policies in physical education reflected this sensibility, departing from the authoritarian character acquired during the dictatorship and promoting, with the democratic opening, individual responsibility and voluntary participation in physical activities. The analysis of government documents is combined with the study of broader cultural phenomena pointing to an increasing commodification of practices, techniques, and knowledge aimed at bodily improvement. The study demonstrates how there was a shift away from state-centered interventions toward the rise of private initiatives in body intervention, facilitated by a climate of growing individualism.
Keywords: Body; neoliberalism; individualism; market; State